Toward a Data-driven Classification of European Higher Education Institutions - Lepori , Benedetto; Lambrechts, Agata (International Higher Education, 2022)
The differentiation of profiles of institutions over the past several decades emphasizes their relevance for higher education. Unlike in the United States, there is currently no broad classification of higher education institutions in Europe. Building on European Tertiary Education Register data, we propose a new comprehensive and cross-country classification in six classes that recognizes the diversity of functions and specializations of institutions within European higher education.